Chemical mechanical polishing composition for metal alloy and polishing method thereof
By adding alumina abrasive particles, oxidants and nanoclays to the chemical mechanical polishing composition, the surface defects and short recycling time of metal alloy substrates in the prior art are solved, and an efficient and environmentally friendly polishing effect is achieved.
Patent Information
- Application Number
- CN202380059680.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-03
- Filing Date
- 2023-12-06
- Publication Date
- 2025-04-11
AI Technical Summary
When the existing chemical mechanical polishing compositions are polished on the surface of metal alloy substrates, they are prone to surface defects, such as pit points and scratches, and their recycling time is short, which increases manufacturing cost and environmental burden.
Using a chemical mechanical polishing composition comprising alumina abrasive particles, an oxidizing agent and nanoclay, the nanoclay has a z-average particle size of up to 1000 nm and a Zeta potential of at least -5 mV, and the composition is substantially free of polymers.
It achieves high material removal rate, long recycling time, low surface defect number and low surface roughness, and is environmentally friendly and has higher economic benefits.
Smart Images

Figure BSB0000210361030000181 
Figure BSB0000210361030000191 
Figure BSB0000210361030000201
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical engineering, and in particular relates to a chemical mechanical polishing composition and a polishing method for metal alloys. Background Art
[0002] Chemical Mechanical Polishing (CMP) is a common process for achieving global planarization in integrated circuit manufacturing or other fields. This process is mainly used to obtain a smooth surface that is flat and free of scratches and impurities. This process polishes various target substrates through a combination of chemical and mechanical forces, and chemical mechanical polishing (CMP) compositions play a decisive role in this process. These compositions are usually aqueous solutions containing various chemical additives and abrasives that are evenly dispersed. CMP compositions are also called polishing slurries, polishing liquids, or polishing compositions, etc., and are commonly used to polish the surfaces of various substrates (such as metals, metal alloys, minerals, and plastics).
[0003] There is a widespread demand for polishing metal substrates, metal alloy substrates, mineral and plastic substrates, such as vehicles, ships, aircraft, pipelines, light reflectors, containers, handrails, kitchen utensils, cooking utensils, architectural metals and jewelry. Most of the metal parts need to be polished. Among them, ferroalloy substrates (such as stainless steel with good corrosion resistance) are widely used in machine tools, cooking utensils, structural materials such as surgical knives, transportation equipment, consumer electronic equipment parts such as smartphone parts, laptop computer shells, metal crafts such as car trademarks, etc., so there is also a demand for polishing the stainless steel surface.
[0004] CMP compositions containing aluminum oxide abrasives are usually used to polish materials containing iron alloys to obtain substrates with smooth mirror surfaces. Many applications of metal alloys require low surface roughness, high brightness and smooth mirror effects, which can be achieved by CMP compositions containing aluminum oxide abrasives. However, aluminum oxide abrasives can easily cause pits, scratches and other surface defects on the surface of metal alloy substrates. Due to lack of oxygen and local destruction of the protective passivation film of stainless steel, such surface defects can cause corrosion problems in ferrous metal alloys such as stainless steel. And in daily use, these surface defect sites are easily contaminated by dirt and bacteria. Therefore, there is still a need for a CMP composition containing aluminum oxide abrasives suitable for surface polishing of metal alloy substrates that can achieve low surface roughness and low number of surface defects.
[0005] In order to reduce manufacturing costs, waste materials and environmental burden, CMP compositions are usually recycled during the polishing process of metal alloy substrates. For example, a CMP composition is used for polishing, then discharged from a polishing device and collected in a tank, and then recycled back to the polishing device for further polishing. Therefore, it is necessary to enable a CMP composition containing aluminum oxide abrasive particles to have a long recycling time. The recycling time refers to the time during which the composition can be used again for chemical mechanical polishing of a substrate without an overall decrease in polishing performance (such as material removal rate). However, during recycling, the activity of the CMP composition often decreases over time, which may be due to wear, cracking and shrinkage of aluminum oxide particles during polishing, or due to chemical changes in aluminum oxide particles. The reduction in the polishing activity of the CMP composition leads to a reduction in the time during which the CMP composition can be recycled for polishing, and replacing the CMP composition will lead to an increase in manufacturing costs and environmental burden. In addition, conventional CMP compositions often add polymers to increase the recycling time of the CMP composition, avoid aggregation of aluminum oxide particles, and reduce the number of defects in the substrate during the CMP process. Such additions usually increase costs, increase environmental burdens, and reduce the material removal rate of the substrate during the CMP process. Therefore, there remains a need for a CMP composition comprising aluminum oxide abrasive grains suitable for polishing metal alloy substrate surfaces that can achieve higher removal rates, longer recycle times, low surface defect counts, and is virtually polymer-free. Summary of the invention
[0006] One object of the present invention is to overcome the above problems existing in the prior art. Preferably, the embodiments of the present invention provide a composition suitable for chemical mechanical polishing of the surface of a metal alloy substrate, which composition exhibits high material removal rate and longer recycling time on the one hand, and can achieve low surface roughness and low number of surface defects on the other hand, and it contains almost no polymer and is more environmentally friendly.
[0007] Specifically, the chemical mechanical polishing composition of the present invention comprises aluminum oxide abrasive grains, an oxidant and a dispersant, wherein the dispersant is nanoclay having a z-average particle size of at most 1000 nm and a Zeta potential value of at least -5 mV.
[0008] Preferably, the aluminum oxide abrasive grains have a Zeta potential of 8 to 80 mV at a pH of 2.5 to 4 in the composition.
[0009] Preferably, the oxidizing agent is not a peroxide compound.
[0010] Preferably, the composition has a pH of 7 at most.
[0011] Preferably, the nanoclay has a D70 of at most 1600 nm as measured by dynamic light scattering.
[0012] Preferably, the composition comprises 0.0001 wt% to 15 wt% nanoclay.
[0013] Preferably, the increase ratio of the aluminum oxide D70 is at most 5.5.
[0014] Preferably, the increase ratio of the aluminum oxide D30 is at most 4.2.
[0015] Preferably, the composition is substantially free of polymers.
[0016] Another object of an embodiment of the present invention is to provide a polishing method for a metal alloy substrate, wherein the method is implemented using the above composition.
[0017] The CMP composition provided by the present invention can not only achieve a high material removal rate in the chemical mechanical polishing of a metal alloy substrate, but also can achieve a low number of surface defects and a longer recycling time in the case of almost no polymer, and is environmentally friendly and has higher economic benefits. The product polished with the CMP composition of the present invention has low surface roughness, low number of surface defects (scratches and pits) and a satisfactory mirror effect. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] The chemical mechanical polishing composition generally comprises abrasive particles dispersed in an aqueous carrier. The abrasive particles can help remove material from the surface of the substrate during polishing. Preferably, the abrasive particles can be metal oxide abrasive particles selected from cerium oxide (ceria), aluminum oxide (aluminum oxide), silicon oxide (silicon dioxide), zirconium oxide (zirconium oxide), titanium oxide (titania), germanium oxide (germanium oxide), magnesium oxide (magnesium oxide), nickel oxide, gallium oxide (gallium oxide), yttrium oxide (yttrium oxide) and combinations thereof. Preferably, the abrasive particles contain at least 67 wt% (weight percentage), more preferably at least 74 wt%, more preferably at least 81 wt%, more preferably at least 88 wt%, and most preferably at least 93 wt% aluminum oxide. In a particularly preferred embodiment, the abrasive particles are all aluminum oxide abrasive particles.
[0020] When used, the composition preferably contains at least 0.02wt%, more preferably at least 0.24wt%, more preferably at least 0.63wt%, more preferably at least 0.82wt%, and most preferably at least 1.0wt% of abrasive particles. The term "when used" as used herein refers to the moment when the composition is applied to the surface of the substrate during chemical mechanical polishing. If the concentration of abrasive particles is too high, the composition may cause undesirable surface defects such as substrate scratches during polishing. Therefore, when used, the composition preferably contains at most 40wt%, more preferably at most 35wt%, more preferably at most 30wt%, more preferably at most 25wt%, and most preferably at most 20wt% of abrasive particles. In a preferred embodiment, the composition contains 0.02wt% to 40wt%, more preferably 0.24wt% to 35wt%, more preferably 0.63wt% to 30wt%, more preferably 0.63wt% to 25wt%, and most preferably 1.0wt% to 20wt% of abrasive particles.
[0021] As known to those skilled in the art, the aluminum oxide abrasive grains may be fumed aluminum oxide or aluminum oxide with different crystal phases, such as α-aluminum oxide, β-aluminum oxide, γ-aluminum oxide, δ-aluminum oxide, θ-aluminum oxide, σ-aluminum oxide, κ-aluminum oxide, η-aluminum oxide, χ-aluminum oxide, p-aluminum oxide, and combinations thereof. Preferably, the aluminum oxide abrasive grains are selected from α-aluminum oxide, β-aluminum oxide, γ-aluminum oxide, δ-aluminum oxide, σ-aluminum oxide, θ-aluminum oxide, and combinations thereof.
[0022] It has been demonstrated that α-alumina can exhibit a higher substrate material removal rate during chemical mechanical polishing compared to alumina abrasive grains having other crystal phases. Therefore, the alumina abrasive grains preferably contain at least 6 wt%, more preferably at least 11 wt% of α-alumina. As known to those skilled in the art, the amount of α-alumina can be obtained by X-ray diffraction (XRD), for example, using a D8 X-ray diffractometer (Bruker Corp) based on the integrated intensity ratio of the (113) plane. However, a large amount of α-alumina can lead to an increase in the number of defects such as scratches and pits on the substrate surface. The inventors have found that the composition of the present invention can exhibit a high material removal rate even when the α-alumina content is low, thereby generating a smaller number of defects on the substrate surface. Therefore, it is preferred that the alumina abrasive grains contain up to 96 wt%, more preferably up to 95 wt% of α-alumina. In a preferred embodiment, the alumina abrasive grains contain 6 wt% to 96 wt%, more preferably 11 wt% to 95 wt%% of α-alumina.
[0023] Preferably, the aluminum oxide abrasive grains contain a mixture of α-aluminum oxide and aluminum oxide having a non-α crystalline phase. The aluminum oxide having a non-α crystalline phase may be any aluminum oxide except α-aluminum oxide, such as β-aluminum oxide, γ-aluminum oxide, δ-aluminum oxide, θ-aluminum oxide, σ-aluminum oxide, κ-aluminum oxide, η-aluminum oxide, χ-aluminum oxide and p-aluminum oxide, or a combination thereof. Preferably, the aluminum oxide having a non-α crystalline phase is selected from β-aluminum oxide, γ-aluminum oxide, δ-aluminum oxide, σ-aluminum oxide, θ-aluminum oxide, and a combination thereof. Preferably, the aluminum oxide abrasive grains contain at least two crystalline phases, more preferably at least three crystalline phases. The inventors have found that the aluminum oxide abrasive grains as described herein can reduce the number of surface defects of the substrate and can reduce the surface roughness of the substrate surface, thereby helping to improve the visual effect of mirror finishing to obtain a bright and reflective surface.
[0024] The average particle size (diameter) of the abrasive particles will affect the material removal rate. As known to those skilled in the art, the average particle size of the abrasive particles can be obtained by measuring the composition by laser diffraction (for example, using LA-960 from Horiba). The curve obtained by this measurement provides the cumulative volume percentage of particles of a certain size, from which the corresponding D10, D30, D50, D70 and D90 values can be obtained. The particle size of the aluminum oxide abrasive particles mentioned here is obtained by the particle size distribution of the aluminum oxide abrasive particles measured in the composition.
[0025] The average particle size (D50) corresponds to a value at which 50% by volume of the particles have a particle size less than this value. A smaller D50 of the aluminum oxide abrasive grains will result in a lower material removal rate. Preferably, the abrasive grains have a D50 of at least 0.09 μm, more preferably at least 0.41 μm, more preferably at least 1.28 μm, more preferably at least 1.72 μm, and most preferably at least 2.01 μm as measured by laser diffraction. However, if the D50 of the aluminum oxide abrasive grains is too large, a large number of undesirable surface defects, such as scratches and pits, will appear during the CMP process. Therefore, the abrasive grains preferably have a D50 of at most 15 μm, more preferably at most 12 μm, more preferably at most 10 μm, more preferably at most 8 μm, and most preferably at most 6 μm as measured by laser diffraction. In a preferred embodiment, the abrasive particles have a D50 measured by laser diffraction of 0.09 μm to 15 μm, more preferably 0.41 μm to 12 μm, more preferably 1.28 μm to 10 μm, more preferably 1.72 μm to 8 μm, more preferably 2.01 μm to 6 μm.
[0026] The numerical value corresponding to D10 is: 10% by volume of the particles have a particle size smaller than this value. Experiments have shown that a smaller D10 of aluminum oxide abrasives can achieve a smaller surface roughness during CMP treatment. The D10 of the aluminum oxide abrasives mentioned here is obtained from the particle size distribution of the aluminum oxide abrasives measured in the composition. Preferably, the abrasive has a D10 measured by laser diffraction of at most 10 μm, more preferably at most 8 μm, more preferably at most 6 μm, more preferably at most 4 μm, and most preferably at most 3 μm. However, a smaller D10 of aluminum oxide abrasives will reduce the material removal rate. Preferably, the abrasive has a D10 measured by laser diffraction of at least 0.005 μm, more preferably at least 0.009 μm, more preferably at least 0.02 μm, more preferably at least 0.04 μm, and most preferably at least 0.08 μm. In a preferred embodiment, the abrasive particles have a D10 measured by laser diffraction of 0.005 μm to 10 μm, more preferably 0.009 μm to 8 μm, more preferably 0.02 μm to 6 μm, more preferably 0.04 μm to 4 μm, most preferably 0.08 μm to 3 μm.
[0027] The numerical value corresponding to D30 is: 30% by volume of the particles have a particle size smaller than this value. Experiments have shown that a smaller D30 of aluminum oxide abrasives can achieve a smaller surface roughness during CMP treatment. The D30 of the aluminum oxide abrasives mentioned here is obtained from the particle size distribution of the aluminum oxide abrasives measured in the composition. Preferably, the abrasive has a D30 measured by laser diffraction of at most 12.5 μm, more preferably at most 11 μm, more preferably at most 9 μm, more preferably 7 μm, and most preferably at most 5 μm. However, a smaller D30 of aluminum oxide abrasives will reduce the material removal rate. Preferably, the abrasive has a D30 measured by laser diffraction of at least 0.009 μm, more preferably at least 0.02 μm, more preferably at least 0.05 μm, more preferably at least 0.81 μm, and most preferably at least 1.12 μm. In a preferred embodiment, the abrasive particles preferably have a D30 measured by laser diffraction of 0.009 μm to 12.5 μm, more preferably 0.02 μm to 11 μm, more preferably 0.05 μm to 9 μm, more preferably 0.81 μm to 7 μm, most preferably 1.12 μm to 5 μm.
[0028] D70 corresponds to a numerical value: 70% by volume of the particles have a particle size smaller than this value. A higher D70 of the aluminum oxide abrasive will result in a higher material removal rate. The D70 of the aluminum oxide abrasive mentioned here is obtained from the particle size distribution of the aluminum oxide abrasive measured in the composition. Preferably, the abrasive has a D70 measured by laser diffraction of at least 0.13 μm, more preferably at least 0.64 μm, more preferably at least 1.58 μm, more preferably at least 2.21 μm, and most preferably at least 2.68 μm. However, if the D70 of the aluminum oxide abrasive is too large, a large number of unfavorable surface defects such as scratches and pits will appear during the CMP process. Preferably, the abrasive has a D70 measured by laser diffraction of at most 19 μm, more preferably at most 16 μm, more preferably at most 13 μm, more preferably at most 10 μm, and most preferably at most 8 μm. In a preferred embodiment, the abrasive particles preferably have a D70 measured by laser diffraction of 0.13 μm to 19 μm, more preferably 0.64 μm to 16 μm, more preferably 1.58 μm to 13 μm, more preferably 2.21 μm to 10 μm, most preferably 2.68 μm to 8 μm.
[0029] D90 corresponds to a numerical value: 90% by volume of the particles have a particle size smaller than this value. A higher D90 of the abrasive grains results in a higher material removal rate. The D90 of the aluminum oxide abrasive grains mentioned here is obtained from the particle size distribution of the aluminum oxide abrasive grains measured in the composition. Preferably, the abrasive grains have a D90 measured by laser diffraction of at least 0.16 μm, more preferably at least 1.58 μm, more preferably at least 2.15 μm, more preferably at least 3.26 μm, and most preferably at least 4.42 μm. However, if the D90 is too large, a large number of unfavorable surface defects such as scratches and pits will appear during the CMP process. Preferably, the abrasive grains have a D90 measured by laser diffraction of at most 25 μm, more preferably at most 21 μm, more preferably at most 18 μm, more preferably at most 15 μm, and most preferably at most 12 μm. In a preferred embodiment, the abrasive particles have a D90 measured by laser diffraction of 0.16 μm to 25 μm, more preferably 1.58 μm to 21 μm, more preferably 2.15 μm to 18 μm, more preferably 3.26 μm to 15 μm, most preferably 4.42 μm to 12 μm.
[0030] The abrasive particles should have a suitable BET surface area. The BET surface area can be measured by a person skilled in the art using the Brunauer-Emmett-Teller method by adsorbing nitrogen on the abrasive particle surface. A larger surface area of the particle can increase the contact area between the particle and the substrate, thereby improving the material removal rate. Therefore, the abrasive particles preferably have a surface area of at least 2.1 m 2 / g, more preferably at least 6.4m 2 / g, more preferably at least 10.1m 2 / g, most preferably at least 16.3m2 The abrasive particles preferably have a BET surface area of at most 94.7 m 2 / g, more preferably up to 81.2m 2 / g, more preferably up to 72.9m 2 / g, most preferably up to 60.6m 2 / g of BET surface area.
[0031] Preferably, the abrasive particles have a positive charge. The charge refers to the zeta potential, which can be measured, for example, by a Mastersizer S (Malvern Instruments). As known to those skilled in the art, the zeta potential of the abrasive particles in the composition refers to the potential at the interface between the mobile fluid in the composition and the fluid stabilizing layer attached to the abrasive particles dispersed in the composition. A higher zeta potential results in a stronger electrostatic repulsion between the particles, thereby increasing the stability of the dispersion of the particles in the composition. Preferably, the abrasive particles have a zeta potential of at least 8 mV, more preferably at least 13 mV, more preferably at least 18 mV, and most preferably at least 26 mV in the composition at a pH of 2.5 to 4. Preferably, the abrasive particles have a zeta potential of at most 80 mV, more preferably at most 75 mV, more preferably at most 70 mV, and most preferably at most 60 mV in the composition at a pH of 2 to 5. Preferably, the abrasive particles have a zeta potential of 8 to 80 mV, more preferably 13 to 75 mV, more preferably 18 to 70 mV, more preferably 26 to 60 mV at a pH of 2.5 to 4 in the composition.
[0032] The composition may also include an oxidant. Depending on the substrate, the oxidant may react with the substrate surface and promote material removal during the polishing process. Preferably, the oxidant is a nitrate compound. Examples of nitrate compounds include iron nitrate, barium nitrate, neodymium praseodymium nitrate, nickel nitrite, potassium nitrate, aluminum nitrate, sodium nitrate, uranyl nitrate, ammonium nitrate, cerium nitrate and combinations thereof. Experiments have shown that compared with other oxidants (e.g., inorganic or organic peroxides), nitrate compounds can make the surface of the substrate less defective during the polishing process, and some nitrate compounds have both an oxidizing effect and a pH regulating effect, which can help the composition achieve a suitable pH. In addition, nitric acid compounds are more stable in the composition than peroxides. Therefore, in a particularly preferred embodiment, the oxidant is not a peroxide. Unsuitable percompounds include, for example, hydrogen peroxide, percarbonates, organic peroxides (e.g., benzoyl peroxide), peracetic acid, di-tert-butyl peroxide, monopersulfates, dipersulfates, sodium peroxide, urea peroxide, persulfates, periodic acid, periodates, perbromic acid, perbromates, perchloric acid, perchlorates, perboric acid, permanganates, perchlorates, perborate salts, and combinations thereof. Preferably, when used, the composition comprises at least 0.05 wt%, more preferably at least 0.3 wt%, more preferably at least 0.84 wt%, more preferably at least 1.56 wt%, most preferably at least 3.0 wt% of the oxidant. Preferably, when used, the composition comprises at most 25 wt%, more preferably at most 20 wt%, more preferably at most 15 wt%, more preferably at most 10 wt%, most preferably at most 8 wt% of the oxidant. In a preferred embodiment, the composition comprises 0.05 wt% to 25 wt%, more preferably 0.3 wt% to 20 wt%, more preferably 0.84 wt% to 15 wt%, more preferably 1.56 wt% to 10 wt%, more preferably 3.0 wt% to 8 wt% of the oxidizing agent.
[0033] The composition comprises an aqueous carrier. The abrasive and chemical additives are suspended in the aqueous carrier. The aqueous carrier enables the abrasive and chemical additives to contact the substrate and the polishing pad during the CMP process. The aqueous carrier can be any component suitable for suspending the abrasive and the oxidant. Examples of the aqueous carrier are water, ethers (such as dioxane and tetrahydrofuran), alcohols (such as methanol and ethanol), and combinations thereof. Preferably, the aqueous carrier contains at least 50 wt%, more preferably at least 70 wt%, more preferably at least 90 wt%, more preferably at least 95 wt%, and most preferably at least 99 wt% of water. Preferably, the water is deionized water.
[0034] The pH of the composition affects the removal rate of the substrate during the CMP process. It has been found that an alkaline pH results in a lower material removal rate. Therefore, the composition preferably has a pH of at most 7.0, more preferably at most 6.5, more preferably at most 6.0, more preferably at most 5.5, more preferably at most 5.0, and most preferably at most 4.5 when used.
[0035] The composition further comprises a dispersant, which helps to disperse the aluminum oxide abrasive grains and keep them stable in solution, thereby improving the shelf life. The dispersant is preferably nanoclay, polyacrylic acid, sodium dodecylbenzene sulfonate, tetrasodium pyrophosphate, sodium hexametaphosphate, or a combination thereof. In a particularly preferred embodiment, the dispersant is nanoclay. Wherein, the term "nanoclay" as used herein refers to clay whose z-average particle size is at most 1000nm. Nanoclay can be any type of clay, such as natural clay, synthetic clay, modified clay or a combination thereof. Examples of nanoclays include kaolin (e.g., kaolin, dickite, halloysite, nacrite), montmorillonite (e.g., saponite, hectorite, laponite, nontronite, beidellite, magnesite, bentonite, andalusite, kyanite, sillimanite, kaolinite, metakaolin, mullite, aluminum silicate, aluminum dihydrate silicate, potassium aluminum silicate, sodium aluminum silicate, calcium aluminum silicate, aluminum silicate oxide, magnesium aluminum silicate, aluminum boro silicate), illite (e.g., micas such as phlogopite, biotite, ferrolithium mica, muscovite, glauconite), chlorite, palygorskite, sepiolite, vermiculite, talc, pyrophyllite, modifications of such clays, and combinations thereof. In a preferred embodiment, the clay is montmorillonite. In a particularly preferred embodiment, the clay is selected from bentonite, laponite, magnesium aluminum silicate, kaolinite, or a combination thereof.
[0036] For example, nanoclay can be purchased from Shengxinxin Chemical Technology Co., Ltd. (Guangzhou, China).
[0037] It was found that the composition comprising nanoclay of the present invention can extend the shelf life of the composition, and it was also found that the nanoclay of the present invention can reduce the decrease in material removal rate during recycling.
[0038] Preferably, when used for polishing, the composition comprises at least 0.0001wt%, more preferably at least 0.001wt%, more preferably at least 0.01wt%, more preferably at least 0.03wt%, most preferably at least 0.05wt% of nanoclay. However, the amount of nanoclay should not be too high because it will hinder the interaction between the abrasive and the substrate surface, thereby reducing the material removal rate during the CMP process. Therefore, when used, the composition preferably comprises at most 15wt%, more preferably at most 13wt%, more preferably at most 12wt%, more preferably at most 11wt%, most preferably at most 10wt% of nanoclay. In a preferred embodiment, the composition comprises 0.0001wt% to 15wt%, more preferably 0.001 to 13wt%, more preferably 0.01wt% to 12wt%, more preferably 0.03wt% to 11wt%, more preferably 0.05wt% to 10wt% of nanoclay.
[0039] The composition should have a high viscosity. The viscosity can be measured in mPa*s (milliPascal seconds) at 25°C using a NDJ-8S viscometer (Shanghai Lichen Instrument Technology Co., Ltd.). The high viscosity of the composition can be achieved, for example, by the nanoclay of the present invention. It was found that the viscosity of the present invention can reduce the aggregation and agglomeration of abrasive particles and achieve fewer defects on the surface of the substrate. Preferably, the composition has a viscosity of at least 2 mPa*s, more preferably at least 5 mPa*s, and most preferably at least 8 mPa*s when measured as a 2% solution at 25°C; preferably, the composition has a viscosity of at most 90 mPa*s, more preferably at most 80 mPa*s, and most preferably at most 70 mPa*s when measured as a 2% solution at 25°C.
[0040] Preferably, the nanoclay is negatively charged. The greater the absolute value of the negative Zeta potential of the nanoclay, the more stable the dispersion system. Preferably, the value of the Zeta potential of the nanoclay is at least -5mV, preferably at least -10mV, more preferably at least -15mV, more preferably at least -20mV, and most preferably at least -22mV.
[0041] The zeta potential, particle size distribution and z-average particle size of the nanoclay can be tested by subjecting a 0.1 wt.% aqueous dispersion of the nanoclay to ultrasonic treatment at 25°C for 30 minutes. The zeta potential, particle size distribution and z-average particle size of the nanoclay are measured for the clay in the aqueous dispersion, not the clay in the composition. The zeta potential of the nanoclay can be measured by a Mastersizer S (Malvern Instruments Ltd., UK); the particle size distribution and z-average particle size can be measured by dynamic light scattering, for example, using a Zetasizer Nano ZSE (Malvern Instruments Ltd.); the Z-average particle size refers to the intensity-weighted average hydrodynamic size of a collection of particles measured by dynamic light scattering (for example, using a Zetasizer Nano ZSE (Malvern Instruments Ltd.). The D10, D30, D50, D70 and D90 of the nanoclay can be obtained from the particle size distribution measured as described above.
[0042] The inventors have found that nanoclays with a smaller z-average particle size can improve the dispersibility of alumina particles, extend the shelf life of the composition, reduce the number of pits on the substrate surface, and reduce surface roughness. It was found that nanoclays with a larger z-average particle size can cause the aggregation and agglomeration of alumina abrasive particles, resulting in a greater increase in the D10, D30, D50, D70, and D90 measured by alumina in the composition, and the increase caused by the increase in surface roughness and surface defects (such as pits). And the inventors have found that nanoclays with nanometer size can improve the surface morphology of stainless steel, while nanoclays with micrometer size can deteriorate the apparent morphology of stainless steel. The nanoclay should have a suitable z-average particle size. Preferably, the nanoclay has a z-average particle size of at most 1100nm, preferably at most 1050nm, preferably at most 1000nm, preferably at most 990nm, preferably at most 980nm, and more preferably at most 970nm measured by dynamic light scattering. However, if the z-average particle size of the clay is too small, it will affect the viscosity of the composition, resulting in an adverse effect. Preferably, the nanoclay has a z-average particle size of at least 1 nm, preferably at least 2 nm, preferably at least 5 nm, preferably at least 10 nm, preferably at least 15 nm, more preferably at least 20 nm measured by dynamic light scattering. In a preferred embodiment, it is preferred that the nanoclay has a z-average particle size of 1 nm to 1100 nm, preferably 2 nm to 1050 nm, preferably 5 nm to 1000 nm, preferably 10 nm to 990 nm, preferably 15 nm to 980 nm, more preferably 20 nm to 970 nm measured by dynamic light scattering.
[0043] Experiments have shown that nanoclays with smaller D10 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D10 of at most 600nm, more preferably at most 550nm, more preferably at most 500nm, more preferably at most 450nm, and most preferably at most 400nm as measured by dynamic light scattering. However, if the D10 of the nanoclay is too small, the material removal rate will be reduced. Preferably, the nanoclay has a D10 of at least 0.01nm, more preferably at least 0.05nm, more preferably at least 0.1nm, more preferably at least 0.5nm, and most preferably at least 1nm as measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D10 of 0.01nm to 600nm, 0.05nm to 550nm, 0.1nm to 500nm, more preferably 0.5nm to 450nm, and more preferably 1nm to 400nm as measured by dynamic light scattering.
[0044] Experiments have shown that nanoclays with smaller D30 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D30 of at most 1100nm, more preferably at most 1050nm, more preferably at most 1000nm, more preferably at most 950nm, and most preferably at most 900nm measured by dynamic light scattering. However, a smaller D30 of the nanoclay will reduce the material removal rate. Preferably, the nanoclay has a D30 of at least 0.05nm, more preferably at least 0.1nm, more preferably at least 0.5nm, more preferably at least 1nm, and most preferably at least 1.3nm measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D30 of 0.05nm to 1100nm, more preferably 0.1nm to 1050nm, more preferably 0.5nm to 1000nm, more preferably 1nm to 950nm, and most preferably 1.3nm to 900nm measured by dynamic light scattering.
[0045] Experiments have shown that nanoclays with smaller D50 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D50 of at most 1300nm, more preferably at most 1200nm, more preferably at most 1100nm, more preferably at most 1000nm, more preferably at most 950nm measured by dynamic light scattering. However, a smaller D50 of the nanoclay will reduce the material removal rate. Preferably, the nanoclay has a D50 of at least 0.1nm, more preferably at least 0.5nm, more preferably at least 1nm, more preferably at least 1.3nm, and most preferably at least 1.5nm measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D50 of 0.1nm to 1300nm, more preferably 0.5nm to 1200nm, more preferably 1nm to 1100nm, more preferably 1.3nm to 1000nm, and most preferably 1.5nm to 950nm as measured by dynamic light scattering.
[0046] Experiments have shown that nanoclays with smaller D70 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D70 of at most 1600nm, more preferably at most 1550nm, more preferably at most 1500nm, more preferably at most 1450nm, and most preferably at most 1400nm measured by dynamic light scattering. However, a smaller D70 of the nanoclay will reduce the material removal rate. Preferably, the nanoclay has a D70 of at least 0.5nm, more preferably at least 1nm, more preferably at least 1.4nm, more preferably at least 1.8nm, and most preferably at least 2nm measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D70 of 0.5nm to 1600nm, more preferably 1nm to 1550nm, more preferably 1.4nm to 1500nm, more preferably 1.8nm to 1450nm, and most preferably 2nm to 1400nm measured by dynamic light scattering.
[0047] Experiments have shown that nanoclays with smaller D90 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D90 of at most 2000nm, more preferably at most 1950nm, more preferably at most 1900nm, more preferably at most 1800nm, and most preferably at most 1700nm measured by dynamic light scattering. However, a smaller D90 of the nanoclay will reduce the material removal rate. Preferably, the nanoclay has a D90 of at least 1nm, more preferably at least 2nm, more preferably at least 3nm, more preferably at least 3.5nm, and most preferably at least 4nm measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D90 of 1nm to 2000nm, more preferably 2nm to 1950nm, more preferably 3nm to 1900nm, more preferably 3.5nm to 1800nm, and most preferably 4nm to 1700nm measured by dynamic light scattering.
[0048] The increase of the aluminum oxide particles D10, D30, D50, D70, and D90 refers to the ratio of the particle size of the aluminum oxide particles in the composition to the particle size of the aluminum oxide particles in the aqueous dispersion (regardless of the composition containing what ingredients), which is specifically obtained by laser diffraction measurement, specifically refers to: the corresponding ratio of the aluminum oxide particle size measured in the composition to the aluminum oxide particle size measured in the aluminum oxide dispersion (85wt.% water) with an aluminum oxide concentration of 15wt.%. The inventors found that a smaller increase ratio is associated with a reduction in the number of pits and a reduction in surface roughness. The inventors found that the nanoclay of the present invention can reduce the increase ratio of aluminum oxide particles D10, D30, D50, D70, and D90. Preferably, the increase ratio of the aluminum oxide D10 in the composition to the aluminum oxide D10 measured in the aluminum oxide dispersion (85wt.% water) with an aluminum oxide concentration of 15wt.% is at most 3.5, more preferably at most 3, more preferably at most 2.5, and most preferably at most 2. Preferably, the ratio of the increase of D30 of alumina in the composition to the D30 of alumina measured in a dispersion of alumina having an alumina concentration of 15 wt.% (85 wt.% water) is at most 4.2, preferably at most 3.5, more preferably at most 3, more preferably at most 2.5. Preferably, the ratio of the increase of D50 of alumina in the composition to the D50 of alumina measured in a dispersion of alumina having an alumina concentration of 15 wt.% (85 wt.% water) is at most 5.5, preferably at most 5, further preferably at most 4.5, and even more preferably at most 4. Preferably, the ratio of the increase of D70 of alumina in the composition to the D70 of alumina measured in a dispersion of alumina having an alumina concentration of 15 wt.% (85 wt.% water) is at most 5.5, preferably at most 5, further preferably at most 4.5, and even more preferably at most 4. Preferably, the increased ratio of D90 of alumina in the composition to D90 of alumina measured in a dispersion of alumina having an alumina concentration of 15 wt.% (85 wt.% water) is at most 5.5, preferably at most 5, further preferably at most 4.5, and most preferably at most 4.
[0049] Preferably, the composition is substantially free of polymers. The polymer may be any polymer. Typically, polymers are used in CMP compositions containing aluminum oxide to improve the dispersibility of the aluminum oxide particles, thereby increasing the shelf life of the composition and preventing particle aggregation that may cause surface defects of the substrate. However, during CMP polishing, polymers typically reduce the material removal rate of the substrate. Surprisingly, it was found that even in the absence of a polymer, the composition according to the present invention caused fewer defects in the substrate surface.
[0050] As used herein, the term "substantially free of component X" refers to a composition that does not substantially contain the component X, ie, such component may at most be present in the composition as an impurity or contaminant but is not added to the composition as a separate component.
[0051] Optionally, the composition comprises a pH adjusting agent. The pH adjusting agent can help the composition achieve a suitable pH. The pH adjusting agent can be an acid or a salt thereof. The acid or a salt thereof can be an organic acid, an inorganic acid or a combination thereof.
[0052] Examples of organic acids are formic acid, acetic acid, propionic acid, butyric acid, valeric acid, methylbutyric acid, caproic acid, dimethylbutyric acid, ethylbutyric acid, methylvaleric acid, heptanoic acid, methylhexanoic acid, caprylic acid, ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, malic acid, phthalic acid, tartaric acid, citric acid, lactic acid, diglycolic acid, furancarboxylic acid, tetrahydrofuranic acid, methoxyacetic acid, methoxyphenylacetic acid, phenoxyacetic acid, methanesulfonic acid, ethanesulfonic acid, sulfosuccinic acid, benzenesulfonic acid, toluenesulfonic acid, phenylphosphonic acid, hydroxyethyldiphosphonic acid, and combinations thereof.
[0053] Examples of inorganic acids are hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, phosphoric acid, and combinations thereof.
[0054] The composition also optionally comprises one or more preservatives. The preservative can be any suitable compound that prevents, inhibits, reduces growth, inhibits activity or eliminates unwanted microorganisms. Examples of suitable preservatives include sodium hypochlorite, methylisothiazolinone, benzisothiazolinone, chloromethylisothiazolinone and combinations thereof. Preferably, the composition comprises at least 0.6ppm by weight, more preferably at least 1.6ppm by weight, more preferably at least 2.7ppm by weight, more preferably at least 3.8 by weight, most preferably at least 4.6ppm by weight of preservative. High concentrations of preservatives can cause undesirable interactions between preservatives and other components of the composition and substrates. Therefore, the composition preferably comprises at most 98ppm by weight, more preferably at most 83ppm by weight, more preferably at most 74ppm by weight, most preferably at most 69ppm by weight of preservative. Ppm used herein refers to ppm by weight.
[0055] The present invention also provides a method for chemical mechanical polishing of a substrate, the method comprising the following steps: (a) providing a chemical mechanical polishing composition; (b) contacting the substrate with the chemical mechanical polishing composition and a polishing pad; (b) moving the polishing pad relative to the substrate with the composition located therebetween; (c) removing at least a portion of the substrate. The CMP composition provided in step (a) is a composition of the present invention. The method may optionally include other steps.
[0056] The composition can be prepared using suitable techniques known to those skilled in the art. The abrasive particles, nanoclays and other chemical additives as described above can be added to the aqueous carrier in any order and in suitable amounts to achieve the desired concentration. The abrasive particles, nanoclays and other chemical additives can be mixed and stirred in the aqueous carrier. The pH value can be adjusted using the above-mentioned pH adjusting agents and pH buffers to obtain and maintain the desired pH. The abrasive particles, nanoclays and other chemical additives can be added at any time before use or during the CMP process.
[0057] The composition can be provided as a one-part system, a two-part system, or a multi-part system. For example, as a two-part system, the first part can include abrasive particles and one or more chemical additives, and the second part can include nanoclay and one or more other chemical additives. The first part and the second part can be mixed at any time before the CMP process or during the CMP process, such as when using a polishing device with multiple supply paths for the CMP composition.
[0058] The composition may be provided as a concentrate and may be diluted with an appropriate amount of water prior to use. The concentration of the components in the composition may be any suitable, for example 2, 3, 10 or 25 times the above-mentioned concentrations for use. For example, the concentrate may contain abrasive particles and chemical additives in concentrations such that after dilution with an appropriate amount of water, the abrasive particles and chemical additives are present in the composition at the above-mentioned concentrations. If the composition is provided, for example, as a two-part system, one or both parts may be provided as a concentrate. The two parts may be provided at different concentrations, for example the first part may be three times concentrated and the second part may be five times concentrated. The two parts may be diluted in any order prior to mixing.
[0059] The composition should achieve high material removal rates for substrates containing ferrous metal alloys, such as stainless steel, carbon steel, leaded steel, tool steel and cast steel during CMP processing. Preferably, the composition exhibits a material removal rate for substrates containing ferrous metal alloys of at least 8 μm / h, more preferably at least 13 μm / h, more preferably at least 21 μm / h, more preferably at least 25 μm / h during CMP processing.
[0060] The present invention also relates to the use of the composition of the present invention. The composition of the present invention can be used to polish various materials. Preferably, the composition of the present invention is used for chemical mechanical polishing of a substrate comprising one or more materials, the material comprising a metal, a semi-metal, a metal alloy, a metal oxide, a semi-metal oxide, a carbide, a mineral, a plastic or a combination thereof. As known to those skilled in the art, chemical mechanical polishing refers to the process of placing a substrate in a CMP apparatus so that it contacts a polishing pad and a CMP composition located therebetween. The polishing pad moves relative to the substrate to remove a portion of the substrate.
[0061] For some materials such as metals, metal alloys, metal oxides and minerals, the compositions are used in a final polishing step, while for other materials such as ceramics and plastics, the compositions are used in intermediate polishing steps.
[0062] Examples of metals, metal alloys and metal oxides that can be polished with the composition of the present invention are iron, iron alloys (e.g., steel), aluminum, aluminum alloys, titanium, titanium alloys, nickel, nickel alloys, copper, copper alloys, Kovar, white copper, Inconel, brass, niobium, bronze, nickel silver, beryllium, monel, vanadium, Hastelloy, tantalum, silver, gold, molybdenum, Nimonic alloys, Waspaloy alloys, tungsten, ceramics, and combinations thereof. The metal oxides can be in the form of single crystals, polycrystalline, sintered bodies (ceramics), or combinations thereof.
[0063] In a particularly preferred embodiment, the present invention is used for chemical mechanical polishing of a substrate comprising a metal alloy. The metal alloy may comprise a metal as its main component and at least one metal different from the main component. The number of metal species different from the main component is not limited, for example, it may be two, three or more. The metal preferably used as the main component of the metal alloy is selected from aluminum, titanium, magnesium, iron, nickel and copper. In a particularly preferred embodiment, the main metal species is iron. Examples of ferroalloys include stainless steel, carbon steel, alloy steel, leaded steel, tool steel, cast steel, maraging steel, cast iron and combinations thereof.
[0064] The present application is described in detail below through specific embodiments.
[0065] Example 1
[0066] Compositions A1-A5 and E1-E6 were evaluated for stainless steel material removal rate, surface roughness, and surface defects. Compositions A1-A5 and E1-E6 included 15 wt% aluminum oxide abrasive particles, 5 wt% potassium nitrate, 0.5 wt% potassium citrate, and 30 ppm (by weight) of a preservative KATHON™ LX 150 (Dow Inc.). The pH of these compositions was 3.5. Except for A1, all other compositions also contained 1 wt% of nanoclay as shown in Table 1. All compositions were free of peroxide compounds and free of polymers.
[0067] The composition without clay was prepared by first adding the chemical additive to deionized water and stirring until the additive was dissolved; then adding the aluminum oxide abrasive to the solution and stirring the composition until the aluminum oxide was dispersed. The composition containing clay was prepared by first stirring to dissolve the chemical additive, then adding the clay, and then adding the aluminum oxide abrasive to the solution; stirring the solution containing the chemical additive and clay until the clay was dispersed.
[0068] The z-average particle size of the nanoclay was measured by dynamic light scattering using a Zetasizer Nano ZSE (Malvern Instruments Ltd., UK) in a 0.1 wt% aqueous dispersion. The zeta potential of the nanoclay was measured in a 0.1 wt% aqueous dispersion using a Mastersizer S (Malvern Instruments Ltd., UK). Prior to measuring the z-average particle size and zeta potential, the nanoclay aqueous dispersion was sonicated for 30 minutes at 25°C to obtain a uniform aqueous dispersion.
[0069] As described above, before adding the aluminum oxide abrasive particles to the composition, the D30, D50, D70 and D90 of the aluminum oxide abrasive particles were obtained by laser diffraction in an 85 wt.% aqueous dispersion using Horiba LA960. After the aluminum oxide particles were dispersed, the D30, D50, D70 and D90 of the aluminum oxide abrasive particles were measured in the composition using Horiba LA960. As described above, the increase ratio of D30, D50, D70 and D90 was obtained by calculating the ratio of the corresponding particle size of the aluminum oxide abrasive particles dispersed in the composition to the corresponding particle size of the aluminum oxide abrasive particles dispersed in the 85 wt.% aqueous dispersion.
[0070] A Nano-Max polishing tool (Shenzhen Nanos Precision Machinery Technology Co., Ltd.) was used to polish the surface of the 9 cm2 surface at a platen speed of 80 rpm, a down force of 2.0 psi, and a slurry flow rate of 100 ml / min. 2 , a stainless steel plate with a thickness of 3 mm was polished for 4 minutes.
[0071] The polished stainless steel plates were visually inspected for surface defects, and the pits and scratches were counted and classified as A = no corresponding defects, B = less than 10 corresponding defects, and C = more than 10 corresponding defects, as shown in Table 1. The material removal rate of the stainless steel plate was measured using an electronic balance, and the weight difference before and after polishing was calculated. The material removal rate is listed in Table 1 as a percentage of the material removal rate of composition A1. The surface roughness (average roughness, Ra) was measured using an SJ-410 surface roughness tester (Mitutoyo Corp) at a measuring length of 25 mm and is listed in Table 1. . As known to those skilled in the art, surface roughness is the arithmetic mean of the absolute value of the deviation of the profile height from the average height within the measuring length. In addition, all surface roughness values below 0.02 can be considered good.
[0072] The stainless steel plates were polished and the relative removal rate, surface roughness, and pits were measured as described above, and the results are shown in Table 1.
[0073] The shelf life of compositions A1-A5 and E1-E6 was evaluated by placing 500 mL of each composition into a 500 mL polyethylene bottle and leaving it at room temperature without stirring. The "shelf life" is defined as the time from when the composition begins to stand until the composition settles and forms a hard cake that is not easily redispersed. The results of the shelf life evaluation are shown in Table 1.
[0074] Table 1
[0075]
[0076]
[0077] From Table 1, it can be seen that the composition of magnesium silicate, bentonite and laponite containing nanoclay with z-average particle size below 1000 nm does not cause pits, and a larger z-average particle size is associated with a larger surface roughness.
[0078] The D30, D50, D70, and D90 of alumina in the composition increase with the size of the nanoclay. Since the D30, D50, D70, and D90 of alumina are measured in the composition, which also contains nanoclay, this indicates that the nanoclay can bind to the surface of the alumina particles and affect the particle size. The larger the nanoclay, the more aggregates there are; the aggregates may contain alumina particles and nanoclay particles.
[0079] From the results of A2-A5, it can be seen that nanoclay with a z-average particle size greater than 1000 nm leads to a significant increase in D30, D50, D70, and D90 of the alumina abrasive particles, indicating that the alumina abrasive particles aggregate and agglomerate, and cause pits and significantly higher surface roughness. From the results of E1-E6, it can be seen that nanoclay with a z-average particle size less than 1000 nm does not lead to a significant increase in the particle size of the alumina abrasive and does not cause pits.
[0080] The shelf life is obtained by observing the composition at room temperature. For composition A1 without nanoclay, the aluminum oxide settled after 5 days and formed a hard cake that was not easily redispersed. All compositions A2-A5 and compositions E1-E6 containing nanoclay were observed for up to 9 months and found to be still dispersed (not settled) after 9 months. After 9 months, no further observation was made on the composition.
[0081] Example 2
[0082] Compositions A6-A8 and E7-E9 were evaluated for stainless steel material removal rate, surface roughness and surface defects. Compositions A6-A8 and E7-E9 included 10 wt% of alumina abrasive particles, 5 wt% of potassium nitrate, 0.1 wt% of potassium citrate, 1.4 wt% of nanoclay as shown in Table 2, and 30 ppm (by weight) of preservative KATHONTM LX150 (Dow Inc.). The pH of these compositions was 3.5. All compositions were free of peroxides and free of polymers. The preparation method of the compositions was the same as in Example 1. Before polishing, the zeta potential of the alumina abrasive particles in the compositions was measured using a Mastersizer S (Malvern Instruments Ltd., UK). The D10, D30, D50, D70 and D90 of the nanoclay in the aqueous dispersion were measured using a Zetasizer Nano ZSE (Malvern Instruments Ltd., UK) under the same conditions as described in Example 1.
[0083] Stainless steel plates were polished for 8 hours using compositions A6-A8 and compositions E7-E9 under the same conditions as described in Example 1, and the ratio of stainless steel material removal rates of compositions A6-A8 and compositions E7-E9 relative to the removal rate of composition A1 in Example 1, surface roughness, and surface defects were evaluated under the same conditions as described in Example 1.
[0084] Table 2
[0085]
[0086] As can be seen from Table 2, the composition containing magnesium silicate, bentonite and laponite with nanoclay D50 less than 1000 nm has a relatively higher composition Zeta potential, does not cause pits, and the polished steel plate has a better surface roughness (Ra≤0.02).
[0087] Example 3
[0088] Compositions E5 and A10 were evaluated for stainless steel removal and pH during recycling. Composition E5 was the same as in Example 1, while composition A10 was a composition containing aluminum oxide purchased from Fujimi Corp. Compositions E5 and A10 were used to polish stainless steel plates under the same conditions as described in Example 1 for 8 hours.
[0089] The composition is recycled and reused during the polishing process, which means that the used composition is collected in a tank and reapplied to the substrate. At the beginning of the polishing process, 500 ml of the composition is applied to the polishing system for polishing. Every 2 hours, an additional 100 ml of the composition is added to the polishing system to compensate for the loss of the recycled composition due to, for example, water evaporation.
[0090] The pH and stainless steel removal rates of the compositions were measured hourly as described in Example 1 and are reported in Table 3, where the relative removal rates are listed as a percentage of the stainless steel removal rate of E5 at 0 hours.
[0091] Table 3
[0092]
[0093] The results show that under substantially the same pH conditions, the removal rate of the composition of Example E5 is always higher than that of Reference Example A10, and the removal rate of the composition of E5 does not decrease in the first two hours, while that of A10 decreases slowly.
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A chemical mechanical polishing composition for a metal alloy surface, comprising aluminum oxide abrasive particles, an oxidizing agent and a dispersant, wherein: The dispersant is a nanoclay having a z-average particle size of at most 1000 nm and a value of the nanoclay Zeta potential of at least -5 mV.
2. The composition according to claim 1, characterized in that The aluminum oxide abrasive particles have a zeta potential of at least 8 mV at a pH of 2.5 to 4 in the composition.
3. The composition according to claim 1, characterized in that The oxidizing agent is not a peroxide.
4. The composition according to claim 1, characterized in that The composition has a pH of 7 at most.
5. The composition according to claim 1, characterized in that The nanoclay has a D70 of at most 1600 nm as measured by dynamic light scattering.
6. The composition according to claim 1, characterized in that The composition comprises 0.0001 wt % to 15 wt % of nanoclay.
7. The composition according to claim 1, characterized in that The increase ratio of the aluminum oxide D70 is at most 5.
5.
8. The composition according to claim 1, characterized in that The increase ratio of the aluminum oxide D30 is at most 4.
2.
9. The composition according to claim 1, characterized in that The composition is substantially free of polymers.
10. A polishing method for a metal alloy substrate, the method being achieved by using the composition according to any one of claims 1 to 9.